INTERPRETASI KATA AL-á¹¢IRÃ‚á¹¬ AL-MUSTAQÃŽM DALAM ALQURAN: APLIKASI SEMANTIK TOSHIHIKO IZUTSU - Muhammad Anwar Idris (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2020)
This paper tries to reveal the meaning of the word al-á¹¢irÃ¢á¹Â  al-MustaqÃ®m . As for the word al-á¹¢irÃ¢á¹ al-MustaqÃ®m and its derivations; as many as 33 well-known words in 21 surah in the Alquran. Of the many mentions of this word in the Quran, of course, it will have a different meaning. So it is necessary to study what exactly the meaning of al-á¹¢irÃ¢á¹Â  al-MustaqÃ®m in Alquran using the semantic theory of Toshihiko Izutsu. This theory explains the existence of the basic meaning and relational meaning of Pragmatics and paradigmatics and Weltanschauung (world of meaning) al-á¹¢irÃ¢á¹ Â al-MustaqÃ®m. The results of this study, that the word al-á¹¢irÃ¢á¹Â  al-MustaqÃ®m in Alquran has the basic meaning of "straight path". The syntagmatic relational meaning of al-á¹¢irÃ¢á¹Â  al-MustaqÃ®m which is included in this journal is: filling in to Allah, tauhid creed, Islam and Alquran. Meanwhile, the paradigmatic relational meaning, synonyms of al-á¹¢irÃ¢á¹Â  al-MustaqÃ®m include: al-á¹¢irÃ¢á¹ Â al-Aziz al-HamÃ®d, al-á¹¢irÃ¢á¹ Â al-SawÃ®, al-TarÃ®q al-MustaqÃ®m, Subul al-SalÃ¢m, SabÃ®l LillÃ¢h. Antonyms of the words al-á¹¢irÃ¢á¹Â  al-MustaqÃ®m include: á¹¢irÃ¢á¹ Â al-Jahim, al-TarÃ®q Jahannam, SabÃ®l at-Thaghut, SabÃ®l al-MufsidÃ®na. Then the weltanschauung (world of meaning) al-á¹¢irÃ¢á¹Â  al-MustaqÃ®m is the Hidayah and the Bridge to Hell.Keywords: Semantic Alquran, al-á¹¢irÃ¢á¹ al-MustaqÃ®m , Straight path. Toshihiko Izutsu.Â Tulisan ini berusaha mengungkapkan makna kata al-á¹¢irÃ¢á¹ al-MustaqÃ®m . Adapun kata al-á¹¢irÃ¢á¹ al-MustaqÃ®m dan derivinasinya disebutkan sebanyak 33 kata yang tersebar dalam 21 surat dalam Alquran. Dari banyaknya penyebutan kata tersebut di dalam Alquran, tentunya akan memiliki makna yang berbeda. Sehingga perlu dikaji apa sebenarnya makna al-á¹¢irÃ¢á¹ al-MustaqÃ®m dalam Alquran dengan menggunakan teori semantik Toshihiko Izutsu. Teori ini menjelaskan tentang adanya makna dasar dan makna relasional pragmatik dan paradigmatik serta Weltanschauung (dunia makna) al-á¹¢irÃ¢á¹ al-MustaqÃ®m. Hasil penelitian ini memperlihatkan bahwa kata al-á¹¢irÃ¢á¹Â  al-MustaqÃ®m dalam Alquran memiliki makna dasar â€œjalan yang lurusâ€. Makna relasional sintagmatik al-á¹¢irÃ¢á¹ al-MustaqÃ®m yang disebutkan dalam jurnal ini yaitu: beribadah kepada Allah, akidah tauhid, agama Islam dan Alquran. Sedangkan makna relasional paradigmatik, sinonim kata al-á¹¢irÃ¢á¹ al-MustaqÃ®m antara lain: al-á¹¢irÃ¢á¹ al-â€™AzÃ®z al-H{amÃ®d, al-á¹¢irÃ¢á¹ al-SawÃ®, al-TarÃ®q al-MustaqÃ®m, Subul al-SalÃ¢m, SabÃ®l LillÃ¢h. Antonim kata al-á¹¢irÃ¢á¹ al-MustaqÃ®m antara lain: á¹¢irÃ¢á¹ al- jahim, al-TarÃ®q Jahannam, SabÃ®l at-ThÃ¢ghu>t, SabÃ®l al-MufsidÃ®na. Kemudian weltanschaung (dunia makna) al-á¹¢irÃ¢á¹Â  al-MustaqÃ®m ialah Hidayah dan Jembatan ke neraka.Kata Kunci: Semantik Alquran, al-á¹¢irÃ¢á¹ al-MustaqÃ®m, Jalan yang lurus, Toshihiko Izutsu.